(untitled) (Fiep Bulletin - online, 2015)
The regular physical activity (PA) is important for quality of life and prevention of several diseases resulting from physical inactivity. The physiology of effort seeks to understand the relationship between energy expenditure (EE) and physical activity (PA) and prevention of diseases caused by physical inactivity (IF). This study aimed to determine and compare the GE dances Xote and Dance Dance Revolution® (DDR) for 20 minutes for each style, 15 children, 11 years old, the State School Madre Belém - Palmas / TO, Brazil. This study has shown an average and standard deviation (SD) of body mass (36.67 ± 6,14kg) and height (148.37 ± 6,65cm). To quantify the GE it was used the accelerometer caltrac® 100/100 plan, achieved levels of GE DDR (55.53 ± 16,20kcal) and Xote (50.60 ± 8,32kcal), we used the statistical package SPSS. Statistical analysis was done by the difference in average student paired t test, adopting a significance level of 0.05. A significant difference was found (p = 0.095) (EPExote = 2.14875 and 4.18486 = EPEDDR). The results demonstrate that both GE dances showed high levels. There was no significant difference for p <0.05.